2023
DOI: 10.1002/cbic.202300158
|View full text |Cite
|
Sign up to set email alerts
|

Resolving Confusion Surroundingd‐Ala‐d‐Ala Ligase Catalysis in Cyanobacterial Mycosporine‐Like Amino Acid (MAA) Biosynthesis

Abstract: Mycosporine-like amino acids (MAAs) are natural UV-absorbing sunscreens that evolved in cyanobacteria and algae to palliate harmful effects from obligatory exposure to solar radiation. Multiple lines of evidence prove that in cyanobacteria all MAAs are derived from mycosporine-glycine, which is typically modified by an ATP-dependent ligase encoded by the gene mysD. The function of the mysD ligase has been experimentally described but haphazardly named based solely upon sequence similarity to the d-alanine-d-al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…This cluster was also automatically located with the antiSMASH analysis, showing considerable sequence similarity (> 75%) to other Nostocales strains. The mysD gene (encoding for the recently renamed mycosporine-glycine-amine ligase, Dextro et al 2023b) was located over 1,500,000 bp downstream from the cluster. This suggested that this gene homolog was probably unrelated to MAA biosynthesis, and more likely associated with other biochemical pathways such as peptidoglycan biosynthesis (Walsh 1989).…”
Section: Resultsmentioning
confidence: 99%
“…This cluster was also automatically located with the antiSMASH analysis, showing considerable sequence similarity (> 75%) to other Nostocales strains. The mysD gene (encoding for the recently renamed mycosporine-glycine-amine ligase, Dextro et al 2023b) was located over 1,500,000 bp downstream from the cluster. This suggested that this gene homolog was probably unrelated to MAA biosynthesis, and more likely associated with other biochemical pathways such as peptidoglycan biosynthesis (Walsh 1989).…”
Section: Resultsmentioning
confidence: 99%